Contaminated Aquatic Sediments - Jaglal, Kendrick (Water environment research, 2011)
A review of the literature published in print and/or online in 2010 on subjects relating to the assessment, evaluation and remediation of contaminated aquatic sediments is presented. The review is divided into the following sections: methodology, policy, chemical distribution, fate and transport, bioavailability, bioaccumulation, toxicity, risk assessment and remediation.